California Real Estate Association meeting at Hotel Sainte Claire - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group photograph of the California Real Estate Association. The members are posing in front of the Hotel Sainte Claire, at 302 South Market Street. The hotel had just been built two years prior to the photograph in 1926. The group members include men and women, dressed in formal attire. A young child dressed in overalls stand close to the group of men on the right. Other buildings can be seen on the left and the right of the hotel. One of the buildings to the right resembles a church. Vehicles are visible on the right of the photograph.